What high school students read in biology - Griniuvienė, O. (Psichologija, 1963)
The article deals with the topic of extra-curricular reading of biology; the data was collected from 23 Lithuanian SSR schools and 4 children's libraries. It examines the period of 1960-1962. The objective of the article is to help biology teachers choose extra-curricular reading.The majority of students (65%) were determined to receive books from the school library. The 5-7 grades students use children's libraries, while older students use massive libraries; 77% of students have personal libraries, but only 1.2% have biology books in therein. Some of the children (2-8%) do not use libraries at all.School libraries have few biology books, on average 2.3% of the books. Book collections grow slowly and without a plan. Biology teachers have little interest in libraries.Students read few biology books. Only 5% of books checked out of the library are bio books, which is not even one per student per year.About 30% of all 5th-9th grade students don't read any bio literature at all. The others do read some, but the rates are higher in 5th-7th grades than in 8th-9th. There's a great variety in the reading levels within schools and even within a grade.  It depends on how well extra-curricular reading is managed by biology teachers.Students' interests are very different depending on age, reading, education, interests, and individual character, so management of reading requires individualization.Students’ answers showed that they do not always correctly understand what they read.Everything mentioned above suggests that the main biology extracurricular literary reading manager must be the biology teacher.
Keywords: biology; teaching biology; reading